1982
DOI: 10.1111/j.1651-2227.1982.tb09643.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Chemotherapy in Cystic Fibrosis Patients

Abstract: Høiby, N., Friis, B., Jensen, K., Koch, C, Møller, N.E., Støvring, S. and Szaff, M. (Statens Seruminstitut, Departments of Clinical Microbiology at Rigshospitalet and Hvidovre Hospital, and Paediatric Department TG, Rigshospitalet, Copenhagen, Denmark). Antimicrobial chemotherapy in cystic fibrosis patients. Acta Paediatr Scand 1982; suppl 301: 75‐100. — Every effort should be undertaken to combat recurrent and chronic bacterial respiratory tract infections in patients with cystic fibrosis because infections a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
27
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(27 citation statements)
references
References 82 publications
0
27
0
Order By: Relevance
“…Despite the use of aggressive antibiotic therapy in the treatment of Pseudomonas infections in CF patients (15), eradication of the organism from the lungs of CF patients is difficult to achieve at present (15,21,25,30). It has been suggested that this is because of the biofilm mode of growth of the organism in the lungs of CF patients (8,19,24).…”
mentioning
confidence: 94%
“…Despite the use of aggressive antibiotic therapy in the treatment of Pseudomonas infections in CF patients (15), eradication of the organism from the lungs of CF patients is difficult to achieve at present (15,21,25,30). It has been suggested that this is because of the biofilm mode of growth of the organism in the lungs of CF patients (8,19,24).…”
mentioning
confidence: 94%
“…,B-Lactam antibiotics in combination with tobramycin are the drugs of choice for the treatment of these patients, but the development of resistance is a common problem (7,9,16). Even when an apparently susceptible P. aeruginosa isolate is cultured from the patients prior to and during the treatment, the P-lactam antibiotics often seem to be ineffective.…”
mentioning
confidence: 99%
“…A total of 43 patients with CF who produced large amounts of purulent (dark green) sputum (3 to 5 ml per sample) entered the study. The patients had suffered from chronic bronchopulmonary P. aeruginosa infection for more than 3 years and had a mean number of precipitating antibodies to P. aeruginosa of 31 (range, 18 to 50 normal values; 0 to 1 precipitins) (7). The patients had previously received between 12 and 30 courses of antibiotics.…”
mentioning
confidence: 99%
See 2 more Smart Citations